2014
DOI: 10.1590/1808-1657000942012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação microbiológica de carne de charque produzida industrialmente

Abstract: ABSTRACT:Charqui is a salted and sun dried meat product, obtained by the dehydration of beef, thus being preserved for a long time. Despite going through steps which hamper microorganisms' growth, it can be contaminated during the processing stages. Therefore, this study was aimed at microbiologically evaluating 25 samples of charqui meat taken from a slaughterhouse in Rio Grande do Norte, Brazil. Samples were analyzed as to the counts of coagulase-positive staphylococci, the MPN of thermotolerant coliforms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…Abrantes et al 10 analyzed 25 samples of charque and observed that the results ranged from 1.47 log CFU/g to 5.24 log CFU/g, which is lower than that observed in the present study.…”
Section: Microbiological Analysiscontrasting
confidence: 85%
See 1 more Smart Citation
“…Abrantes et al 10 analyzed 25 samples of charque and observed that the results ranged from 1.47 log CFU/g to 5.24 log CFU/g, which is lower than that observed in the present study.…”
Section: Microbiological Analysiscontrasting
confidence: 85%
“…The technical and legal aspects of food require the standardization of parameters so that the analysis can be made assuring that the products are always in compliance with quality and identity standards 8 . The microbiological analysis of a food makes it possible to guarantee the safety and stability of the product through a qualitative and/or quantitative evaluation of the microbiota present, ensuring that the food matrix complies with the standards established by the legislation 9,10 . Foods, products directly related to health, as foreseen in the legislation 11 , have their control as competence of sanitary surveillance and, for this reason, it must use its tools to ensure that all products available to the population are in accordance with the standards required by the legislation, making them safe for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…From this amount, the production of sundried meat and/or other cured products, traditionally made by hand, is excluded. Salted meats are commonly consumed in the geographic regions of the Northeast and North of Brazil, or by northeastern populations settled in other regions of the country (Associação Nacional das Indústrias de Carne Seca, 2017) Despite the meats being subjected to the dehydration process through salting, what varies between the products is the type of raw material, the ingredients (type and quantity) and the type of processing (time and variations in the drying processes), which end, gives them their own color and flavor (Abrantes et al, 2014).…”
Section: Salt and Charquementioning
confidence: 99%
“…Despite being one of the most consumed industrialized meat products in the country, its expansion in the consumer market is far from being fully explored. Its potential goes beyond the domestic market, being a product that does not require the use of the cold chain for its preservation (Abrantes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being one of the most consumed industrialized meat products in Brazil, its expansion in the consumer market is far from being fully explored. Its potential goes beyond the domestic market, being a product that does not require the use of the cold chain for its preservation (Abrantes et al, 2014). These products are responsible for adding value to meat production and reducing the environmental impact caused by the by-products' disposal (Toldrá et al, 2012).…”
Section: Introductionmentioning
confidence: 99%